May position of hemodialysis catheter tip have a direct effect on its patency? Positive results of a preliminary study on its rotation - Mohammad Hassani (European Journal of Translational Myology, 2022)
Renal transplant therapy is essential in patients with End-Stage Renal Disease (ESRD). It is used in patients awaiting a kidney transplant or those who cannot be a transplant candidate. Central venous catheter is one of the most used access routes worldwide but has been recorded as the one with highest mortality and morbidity rate. Thromboembolic events have played a major part for that. This is a descriptive-analytical study, which conducted in a university treatment center in Tehran, Iran. A total of 225 patients were selected for this study that 108 were excluded because of our criteria. Statistical analysis was performed by SPSS v19 and a total of 117 patients were included in this study. The average age of the patients was 51.62±11.26. 79 (67.5%) and 38 (32.5%) patients had medial and lateral tip direction, respectively. The catheter of 85(72.6%) and 32(27.4%) patients was patent and occluded, respectively. The average catheter tip occlusion time in both groups was 22.5 and 7.5 months. Three-month, six-month, twelve-month, and twenty-four-month patency rate were 99%, 94%, 88%, and 30%, respectively. our findings suggest that medial direction of the tip of the catheter reduces complications caused in CVS. Because our study has been conducted in a small scale and there is lack of similar studies, our team suggests extension to a larger scale to confirm or not our results.